Correlation of Fasting and Postprandial Glucose Levels with Glycosylated Hemoglobin in Diagnosis of Diabetes - Poudyal, Prija; Shrestha, Kabina; Rajbanshi, Lily; Anwar, Afaque (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Diabetes Mellitus describes a group of metabolic disorders characterized by hyperglycemia. Uncontrolled glycemic state often leads to micro and macro vascular complications. Diabetes is the foremost cause of new blindness in adults. Constant screening of the diabetic profile through blood tests of the affected people and prompt actions to control them can help to improve the quality of life of these patients. The study was done to evaluate the correlation between fasting and postprandial plasma glucose levels with glycosylated hemoglobin for diagnosis of diabetes and to determine the prevalence of diabetes in different age groups with sex predilection. Methods: A descriptive cross sectional study was conducted and the data collection was carried out in the Department of Ophthalmic Pathology and Laboratory Medicine, Biratnagar Eye Hospital. Ethical approval was obtained from Institutional Review Committee of this hospital. All 275 patients who attended the laboratory from January 2019 to June 2019 for fasting plasma glucose, postprandial plasma glucose and glycosylated hemoglobin values estimation were included in this study. The data obtained were computed and analyzed using Statistical Package for the Social Sciences version 20.0 Results: A significant correlation between fasting plasma glucose, postprandial plasma glucose and glycosylated hemoglobin was observed in this study (p value <0.001). The correlation coefficient between fasting plasma glucose and glycosylated hemoglobin (r= 0.728) is stronger than the correlation coefficient between postprandial plasma glucose and glycosylated hemoglobin (r= 0.709). Conclusions: Fasting plasma glucose correlated better than postprandial plasma glucose with glycosylated hemoglobin.